Insurrección, legitimidad y política radical - Ramírez Gallegos, Franklin (2005)
This article accomplishes a test of the political legitimacy in April insurrection. For that matter, some issues have bee taken and articulated from political contemporary philosophy and the political sociology of protest. This work allows us to think deeper about the place of insurrection, the resistance and/or the civil rebellion within democratic societies. It therefore privileges the normative evaluation about: a) The way and methods how the rebellion in Quito grew on the streets; b) The political time and the occasion in which these actions took place; and, c) The political responsibility assumed over the implications and effects of anti–establishment actions that finished with a new government overthrown in Ecuador. According to this analysis and considering the political unrest initiated with the first presidential dismissal back in 1997, it has been shown that a new sudden way of sovereignty exercise has been established in the political order that considers a radical way of controlling the political elites, that is “the insurrection way”.